Single Input Fuzzy Logic Controller for Flexible Joint Manipulator - Mohd Riduwan, Ghazali; Mohd Helmi, Suid; Zuwairie, Ibrahim; Muhammad Salihin, Saealal; Mohd Zaidi, Mohd Tumari (IJICIC, 2016)
Joint elasticity in the dynamics of robots manipulator makes the conventional model-based control strategies complex and difficult to synthesize. This paper presents investigations into the development of single input fuzzy logic controller (SIFLC) for tip angular position tracking and deflection angle reduction of a flexible joint manipulator system. A Quanser flexible joint manipulator system is considered and the dynamic model of the system is derived using the Euler-Lagrange formulation. The proposed method, known as the SIFLC, reduces the conventional two-input FLC (CFLC) to a single input single output (SISO) controller. Two parallel SIFLC are developed for both tip angular position and deflection angle control. The proposed control scheme is also compared with existing results by Ahmad et al., which are hybrid proportional-derivative (PD) with low-pass filter (LPF) and PD with non-collocated fuzzy logic control schemes. The performances of the control schemes are assessed in terms of tip angular tracking capability, level of deflection angle reduction and time response specifications. Finally, a comparative assessment of the control techniques is presented and discussed.